If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 119 + -6x = 30x + -23 Reorder the terms: 119 + -6x = -23 + 30x Solving 119 + -6x = -23 + 30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30x' to each side of the equation. 119 + -6x + -30x = -23 + 30x + -30x Combine like terms: -6x + -30x = -36x 119 + -36x = -23 + 30x + -30x Combine like terms: 30x + -30x = 0 119 + -36x = -23 + 0 119 + -36x = -23 Add '-119' to each side of the equation. 119 + -119 + -36x = -23 + -119 Combine like terms: 119 + -119 = 0 0 + -36x = -23 + -119 -36x = -23 + -119 Combine like terms: -23 + -119 = -142 -36x = -142 Divide each side by '-36'. x = 3.944444444 Simplifying x = 3.944444444
| F-0.5=1.2 | | 3x^2+432=0 | | 0.4x+0.3=-0.1 | | 45=(20x) | | x+1.3=5.7 | | 144y^2+25=0 | | 2d+10e+8d+11e= | | 5/6x=-1/6 | | 3.1x+1=2.1x | | 3x+39=6x-9 | | 115-3x=24x+17 | | 115-5x=13x+21 | | 2x+8=778-5x | | 112-(9/5) | | x/2+12=-12 | | 9x+4y=5 | | 6=r+14 | | 3x+11=119-10x | | 8-10x=35-31x | | X-3n=5n | | 3x-3=3x^2-6x+3 | | 4(t-13)=9(t-3) | | 20-4y=4y-36 | | 5(t-5)=8(t+4) | | 3/5t+7=-8 | | 3(t+42)=7(t+126) | | 68-6x=39x+18 | | 90-2x=4x-24 | | 2x^4-18x^2+5=0 | | 3x+31=10-39 | | 3x-x=44-12 | | x+12+3x= |